TOPICAL TIMOLOL EYE DROP SOLUTION FOR THE TREATMENT OF FISSURES IN PATIENTS WITH HAND DERMATITIS - Abdalla, Darsim Mohammed (Journal of Sulaimani Medical College, 2022)
Background Some patients with chronic hand dermatitis may complain of painful and itchy fissures; in some cases, the fissures are reluctant to conventional therapies of hand dermatitis. Objectives To evaluate the efficacy and safety of topical timolol eye drop 0.05% solution for the treatment of fissures in patients with hand dermatitis. Patients and Methods In this therapeutic trial, twenty-two cases with chronic hand dermatitis whose hand fissures are unresponsive to conventional therapies are treated with a single daily application of topical timolol eye drop 0.05% solution on the fissures for three weeks; those with complete disappearance of the fissures and symptoms are regarded as complete response, those with a decrease in size and number of fissures with partial or no improvement of symptoms are regarded as a partial response, and those with no change in size and number of fissures with no improvement in symptoms are regarded as no response, search of any side effect done. Results The age of the patients ranged from 16-39 years, and the majority were females. Eleven patients (50%) showed complete response, eight patients (36.4%) had a partial response, and three patients (13.6%) had no response. Patients with a single fissure had a statistically significant better response than those with multiple fissures. No, local or systemic side effects were recorded. Conclusion Topical timolol solution is an effective and safe choice for treating fissures in patients with hand dermatitis.
Keywords: Timolol eye drop solution; Hand dermatitis; fissures